Iris recognition: a general overview - Horst, Jesse (My University, 2006)
This article reviewed the literature regarding iris recognition. The process of iris recognition is discussed in the context of the mathematical principles that underlie this procedure. Possible applications for iris recognition are explored.
Keywords: Iris (Eye)--Mathematical models; Biometric identification; Iris (Eye)--Identification